Monocyte Subsets, Stanford-A Acute Aortic Dissection, and Carotid Artery Stenosis: New Evidences - Noemi Cifani; Maria Proietta; Maurizio Taurino; Luigi Tritapepe; Flavia Del Porto (Journal of Immunology Research)
Monocytes are a heterogeneous cell population distinguished into three subsets with distinctive phenotypic and functional properties: “classical” (CD14++CD16-), “intermediate” (CD14++CD16+), and “nonclassical” (CD14+CD16++). Monocyte subsets play a pivotal role in many inflammatory systemic diseases including atherosclerosis (ATS). Only a low number of studies evaluated monocyte behavior in patients affected by cardiovascular diseases, and data about their role in acute aortic dissection (AAD) are lacking. Thus, the aim of this study was to investigate CD14++CD16-, CD14++CD16+, and CD14+CD16++ cells in patients with Stanford-A AAD and in patients with carotid artery stenosis (CAS). Methods. 20 patients with carotid artery stenosis (CAS group), 17 patients with Stanford-A AAD (AAD group), and 17 subjects with traditional cardiovascular risk factors (RF group) were enrolled. Monocyte subset frequency was determined by flow cytometry. Results. Classical monocytes were significantly increased in the AAD group versus CAS and RF groups, whereas intermediate monocytes were significantly decreased in the AAD group versus CAS and RF groups. Conclusions. Results of this study identify in AAD patients a peculiar monocyte array that can partly explain depletion of T CD4+ lymphocyte subpopulations observed in patients affected by AAD.